2018
DOI: 10.1007/s10517-018-4190-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined Effect of NF-κB Inhibitor and β2-Adrenoreceptor Agonist on Mouse Mortality and Blood Concentration of Proinflammatory Cytokines in Sepsis

Abstract: Experiments on random-bred albino mice showed that NF-κB inhibitor (BAY 11-7082) and β2-adrenoreceptor agonist (dexmedetomidine hydrochloride) significantly reduced mouse mortality in 4 and 24 h after sepsis modeling (intraperitoneal administration of E. coli) by reducing blood levels of proinflammatory cytokines TNFα, IL-1β, and IL-6. The combined administration of NF-κB inhibitor and β2-adrenoreceptors agonist have an additive effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 15 publications
2
23
0
Order By: Relevance
“…However, the effect of AIF-1 on NF-kB pathway and inflammation can be alleviated by the BAY 11-7082, a NF-kB signaling inhibitor. It is consistent with that BAY 11-7082 has been reported to attenuate the elevated levels of IL-6 and TNF-a (Kumar et al, 2012;Ren et al, 2018;Zabrodskii et al, 2018). Previous studies have demonstrated that AIF-1 is encoded in the region of chromosome 6p21.3, which is clustered with genes related to the inflammatory responses in human (Iris et al, 1993;Deininger et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, the effect of AIF-1 on NF-kB pathway and inflammation can be alleviated by the BAY 11-7082, a NF-kB signaling inhibitor. It is consistent with that BAY 11-7082 has been reported to attenuate the elevated levels of IL-6 and TNF-a (Kumar et al, 2012;Ren et al, 2018;Zabrodskii et al, 2018). Previous studies have demonstrated that AIF-1 is encoded in the region of chromosome 6p21.3, which is clustered with genes related to the inflammatory responses in human (Iris et al, 1993;Deininger et al, 2002).…”
Section: Discussionsupporting
confidence: 89%
“…Interestingly, the production of IL-6 and TNF-a were decreased after BAY 11-7082 treatment. It is consistent with that BAY 11-7082 has been reported to attenuate the elevated levels of IL-6 and TNF-a (Kumar et al, 2012;Ren et al, 2018;Zabrodskii et al, 2018). Specifically, data revealed that peritoneal mesothelial cells, as an important cellular model, were shown to be related with fibrotic change in mouse peritoneal mesothelial cells (Bot et al, 2003;Shin et al, 2017;Zhang et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Numerous studies have shown that the established effects are associated with acetylcholine m1AChRs activation of the brain, 18,21 α7nAChRs of MMS cells, nAChRs of adrenal medulla and other mechanisms. [9][10][11]14,16,17,19 The implementation of the reduction of pro-inflammatory cytokines TNF-α, IL-1β, IL-6, and others (the occurrence of anti-inflammatory effect) is provided by JAK2 kinase, STAT3 transcription factor, transcription factor NF-κB). 5,10,[15][16][17][18][19] In addition, the decrease in mortality from sepsis after acute intoxication of OPC due to the suppression of the synthesis of proinflammatory cytokines is also associated with the effect of corticosteroids (activation of the hypothalamic-pituitaryadrenal system).…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] There is no doubt that research into the mechanisms of the formation of a post intoxication immunodeficiency state in the poisoning of OPC, in particular, the function of phagocyticmonocyte system (PMS) for the purpose of prevention and treatment, resulting in various infectious complications and diseases. 2,3 With the chronic effect of the OPC, the implementation of the cholinergic antiinflammatory pathway (mechanism), [4][5][6][7][8][9][10][11][12][13] which includes: activation of m-cholinergic receptors (mAChRs) of the brain , which modulate the immunoregulatory function of the vagus nerve; excitation of efferent fibers n. vagus; the action of acetylcholine on receptors; the activation of n-cholinergic receptors (in particular, α7nAChRs) of PMS cells. In PMS cells, the onset of an anti-inflammatory effect is provided by kinase JAK2; transcription factor STAT3; transcription factor NF-κB.…”
Section: Introductionmentioning
confidence: 99%